Tomographic imaging of lunulae in capybara knees - Sesoko, Natalia Ferreira [UNESP]; Souza, Livia Pasini de [UNESP]; Pinheiro De Araujo, Fabio Andre [UNESP]; Rahal, Sheila Canevese [UNESP]; Vulcano, Luiz Carlos [UNESP]; Teixeira, Carlos Roberto [UNESP] (Univ Federal Rural Pernambuco, 2011)
The lunulae, ossification of the meniscus, are found in several species of rodents. Some studies suggest that the lunulae may be anatomical features, because there are not any pathological findings in microscopy. The objective of this study was to investigate the presence of lunulae in capybara knees, the world's largest rodent, by simple tomographic scans and three-dimensional reconstruction. For this purpose, we used two adult capybaras, in which both knees were evaluated. The lunulae were visualized with three-dimensional images, and revealed a total of two cranially. With the presence of lunulae confirmed, the capybara may be included in the group of rodents that have this structural feature, which can also contribute to the distinction between pathological processes and normal anatomic structures on imaging tests.
Keywords: Capybara; computed tomography; 3D reconstruction; lunulae